(untitled) (Al-Academy, 2022)
Literary works include, for the most part, text thresholds, which are the first entry into reading them and understanding their connotations, and (literary works) vary according to text thresholds, some of which are limited to the title and on the cover page only, and others, in addition to these two thresholds, are based on the dedication threshold too, and others ... This study takes the story of "Mamo Zain" of the poet Ahmed Al-Khani and his translator Sheikh Muhammad Ramadan Al-Bouti as the field of study, as it is a unique literary work, which included a number of textual thresholds which supported each other and cooperated with the content of the work. The threshold of dedication in the story of "Mamo Zain" was a speech, beside the title, the cover page and the text, and it was in harmony with the title, the cover page and the content, in which the social issue that the text dealt with manifested itself, as it was revealed in the subtitle (a love story that grew on earth and blossomed in heaven). . The (study) will attempt to identify the connotations of the textual thresholds of the work studied, and to show their relation to the text. To conclude that textual thresholds have a role in text comprehension, they often reduce the meaning of the text, and present a picture of its consistency (the text), in terms of the connection of its content with its thresholds